Energy and sustainable development in Latin America and the Caribbean (1999)
Provides an overview of the achievements with regard to sustainability, the flows, the opportunities, the shortages and policy trends. Looks at what can be done to improve the situation and presents guidelines for an energy policy aimed at ensuring sustainable development.
Keywords: ENERGY